تحديد مستويات جودة بحيرة سد بلوران لأغراض الشرب - عوض عادل; جناد هيثم; مجبور عبلة (Latakia University Journal -Engineering Sciences Series, 2019)
يهدف البحث إلى تقييم مياه بحيرة سد بلوران وتحديد مستويات الجودة بهدف الاستخدام (الشرب)، وفق مؤشر جودة عالمي(NSFWQI: National Sanitation Foundation Water Quality Index)، وهو معتمد من قبل المؤسسة العالمية للدراسات العلمية(NSF:National Science Foudation Studies)، ووكالة حماية البيئة (EPA: Environmental Protection Agency). ولذلك تضمن البحث إجراء تحاليل دورية فيزيائية-كيميائية وجرثومية، لمعرفة تغيرات تركيز الباراميترات التسعة المعتمدة في حساب هذا المؤشر. تم قطف العينات في أربعة مواقع على البحيرة، بالإضافة إلى عينتين إضافيتين على نهري قره جالية ورافد نهر قنديل، لمدة عام كامل ابتداءً من نيسان 2010 وحتى آذار 2011. وقد تم قياس (درجة حرارة الماء، درجة الحموضة، الأوكسجن المنحل، العكارة، المواد الصلبة المعلقة)، كما تم تحديد تركيز كل من النترات (3NO) والفوسفور الكلي (TP) واختبار تعداد العصيات الجرثومية الغائطية (F.C)، بالإضافة إلى تحديد الطلب الحيوي للأوكسجن (BOD5). التجارب أجريت وفق الطرق القياسية الأمريكية المعتمدة عالمياً لتحليل مياه الشرب(APHA.1992). تم تمثيل النتائج بيانياً، ثم صنفت البحيرة وفق مؤشر الجودة العالمي بهدف الاستخدام، (NSFWQI)، وكانت من الدرجة الرابعة (D) و الوصف (سيء)، وبالتالي مياه البحيرة غير صالحة للشرب وتحتاج إلى معالجة، بسبب ارتفاع قيم المؤشرات (BOD5، F.C، العكارة، المواد الصلبة المعلقةTSS) عن الحدود المسموحة، ووجد أن تراجع جودة مياه البحيرة ناتج عن النشاط السياحي والزراعي قرب البحيرة. بعد مناقشة النتائج توصلنا لمجموعة استنتاجات وتوصيات بهدف حماية البحيرة والوصول بها إلى مستويات جودة مقبولة. This research includes carrying out periodical physio-chemical and bacterial water tests of the lake of Ballouran Dam at four sites along the lake in addition to two extra samples of the rivers Kara-Jalia and the tributary of Kandil river for a period of an entire year commencing from April 2010 to March 2011. The following indicators were measured: (Temperature, PH, DO, Turbidity, and Total suspended solids). The concentrations of the following ions: (NO3-,TP) and the count test of Fecal Coliform bacteria (F.C) in addition to determining the Biological Oxygen Demand BOD5 were also examined. According to the Syrian Specifications Standard, the results obtained were represented diagrammatically, and then the resulting values were compared with the allowable values of potable water. Then the lake was classed according to the international quality index (NSFWQI: National Sanitation Foundation Water Quality Index) and was at the fourth grade (D) and the description was (bad). Consequently, the water of the lake was not good for drinking and needs treatment due to the indicators (BOD5, F.C, Turbidity, and TSS) rising above the allowable limits. Our finding highlighted the deterioration of water quality in the lake due to human activities. Having discussed the results, we drew a series of conclusions and recommendations for the protecting the lake in order to make it meet acceptable quality levels.